Lower daily energy expenditure as measured by a respiratory chamber in subjects with spinal cord injury compared with control subjects. - Monroe MB; Tataranni PA; Pratley R; Manore MM; Skinner JS; Ravussin E (American Journal of Clinical Nutrition)
BACKGROUND: This study was designed to determine the effect of chronic spinal cord injury on daily energy expenditure. OBJECTIVE: We hypothesized that both resting and total energy expenditure would be lower in spinal cord-injured (SCI) subjects than in control subjects because of lower sympathetic nervous system activity and reduced levels of physical activity in SCI subjects. DESIGN: Twenty-four-hour energy expenditure (24-h EE), resting metabolic rate (RMR), sleeping metabolic rate, spontaneous physical activity, the thermic effect of food (TEF), and 24-h respiratory quotient were measured by using a respiratory chamber in 10 male SCI subjects (injury ranged from level C6 to L3) and 59 age-matched, noninjured, male control subjects. RESULTS: The 24-h EE was lower in SCI than in control subjects (7824 +/- 305 compared with 9941 +/- 188 kJ, P < 0.01). After adjustment for fat-free mass, fat mass, and age, 24-h EE was still lower (-753 kJ/d, P < 0.01) in SCI than in control subjects. Spontaneous physical activity measured by a radar system was also significantly lower (4.6 +/- 0.6% compared with 6.5 +/- 0.3% of time, P < 0.01) in SCI than in control subjects. In absolute value (7347 +/- 268 compared with 9251 +/- 1326 kJ/d, P < 0.01) or after adjustment for fat-free mass, fat mass, and age (-678 kJ/d, P < 0.01), RMR was also lower in SCI than in control subjects. TEF was significantly lower in SCI than in control subjects (987 +/- 142 compared with 1544 +/- 213 kJ/d, representing 12.9% and 15.9% of total energy intake, respectively, P < 0.05). The sleeping metabolic rate and 24-h respiratory quotient did not differ significantly between groups. CONCLUSIONS: The 24-h EE was significantly lower in SCI than in control subjects. This difference can be explained by the lower levels of physical activity, and lower RMR and TEF values, in SCI subjects. Copyright (c) 1998 American Society for Clinical Nutrition